Gender Perception on Flexi and Virtual Time and Work Life Balance - Jyoti; Jaya; Arora, Madhu (Asian Review of Mechanical Engineering, 2021)
The research is aimed to study perception of males and females regarding Flexi time and work-lifebalance. The research is descriptive in nature and data is collected from 380 working professionals using questionnaire on google forms (including males and females). T test is used to know the empirical results. It is found that Although flexi work arrangements are important for reducing attrition rate but along with that a strong policy is also required to cope up with the challenges faced in the workplace.